1998
DOI: 10.1016/s1059-1311(98)80010-1
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy classification and factors associated with control in Saudi adult patients

Abstract: There is insufficient information on the epilepsies in Saudi Arabia. The objectives were to classify the patients according to seizure types and epilepsies as well as to determine the factors associated with control. In a hospital-based study, clinical information, electroencephalographic and neuroimaging findings were utilized to classify the cases into seizure types and epilepsies according to ILAE criteria and to determine the factors statistically associated with control. In the study there were 826 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In other words, the stigma occasionally extends beyond the individual to family members. It is interesting that some Saudi researchers (Jan, 2005;Abduljabbar, M. 1998) attributed the prevalence of epilepsy in Saudi Arabia to the high rate of consanguinity among Saudi people.…”
Section: The Social and Cultural Aspects Of Epilepsy In Saudi Arabiamentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the stigma occasionally extends beyond the individual to family members. It is interesting that some Saudi researchers (Jan, 2005;Abduljabbar, M. 1998) attributed the prevalence of epilepsy in Saudi Arabia to the high rate of consanguinity among Saudi people.…”
Section: The Social and Cultural Aspects Of Epilepsy In Saudi Arabiamentioning
confidence: 99%
“…Apart from Escandall's (2001) narrative account about neuropsychological evaluation in Saudi Arabia, no study so far has addressed the unique sociocultural features of the Saudi society in relation to the practice of neuropsychology in general, and the neuropsychological evaluation in epilepsy surgery in particular. However, epilepsy is a common neurological disorder in Saudi Arabia, as is the case with regard to other neurological disorders, due to the high rate of consanguinity (Jan, 2005;Abduljabbar, 1998). The published rate of prevalence of epilepsy in Saudi Arabia is 6.54 per 1000 population (Al Rajeh et al, 2001), which may help in approximating an estimate for seizure treatment gap in the country.…”
Section: Introductionmentioning
confidence: 99%
“…When it was 3 months of terminal remis- Table 5. Remission (R) as seizure-free period during follow-up 80% -1 year R with 1 year minimum follow-up ͉ Abduljabbar et al [34], 1998 (mixed) 78% -1 year R (during the last 10 of min. 20 years) follow-up ͉ Sillanpaa [11], 1993 (mixed) 74% -2 years R with 2 years minimum follow-up ͉ Berg et al [35], 2001 (prospective) 68% -2 years R by 5 years of follow-up ͉ Collaborative Group for the Study of Epilepsy [36], 1992 (mixed) 51% -3 years R by 5 years of follow-up ͉ Collaborative Group for the Study of Epilepsy [36], 1992 (mixed) Table 6.…”
Section: Remission On or Off Medicationmentioning
confidence: 99%
“…2 Without treatment, the probability of long-term remission is 30-42% [3][4][5] while with treatment, it is 65-80%. [6][7][8][9][10] A large proportion of people with untreated epilepsy will therefore experience continued seizures and this may have enormous implications for outcome when treatment is instituted eventually. 4 Studies of the prognosis of epilepsy have demonstrated a significant increase in risk for seizure recurrence with increasing numbers of seizures 11 and a decrease in the likelihood of remission following treatment in individuals with large numbers of seizures prior to treatment.…”
Section: Introductionmentioning
confidence: 99%